Democracy in Lesotho: theory and practice of opposition - Mohapi, Refiloe Alphonce (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2006)
Using theoretical insights from elsewhere, this thesis examines and explains Lesotho's opposition. It argues that the decline of single-member constituency and the rise of Mixed Member Proportionality (MMP) has weakened the prospects for a strong opposition in Lesotho; more parties in parliament have strengthened the hold of the ruling party. These parties cannot overturn the parliamentary decisions of the ruling Lesotho Congress for Democracy (LCD), which continues to win more than 90% of majority seats in successive elections. So, most bills and motions passed in parliament have support of the majority of the MPs of LCD. Opposition parties have little legislative impact in challenging the policies of government. Paradoxically, MPs of the LCD are often the only source of opposition in the country's parliament.
Keywords: Democracy -- Lesotho; Political parties -- Lesotho; Lesotho -- Politics and government